Liberation theology of disability and the option for the poor - Scot Danforth (Disability Studies Quarterly, 2005)
A liberation theology of disability provides a spiritual discourse that unites a critical analysis of the economic dimensions of disability oppression with an appreciation for the lived experience of disabled persons. This paper builds from prior liberation theology scholarship and the Catholic theological concept called the preferential option for the poor to articulate a liberation theology of disability marked by critical social analysis, humility, hope, and love.
Keywords: Liberation theology of disability; preferential option for the poor; religion and disability; spiritual discourse